THE EFFECT OF COLLABORATIVE LEARNING ON STUDENTS’ SPEAKING PERFORMANCE IN ENGLISH CLASSROOM AT THE SEVENTH GRADE OF SMP NEGERI 2 KELARA - Patmala, Kiki; Ilmiah; Junaid (Journal of Language Testing and Assessment, 2025)
This researcher aims to determine whether there is an increase in Fluency and Accuracy by using the Collaborative Learning Method for class VII students at SMP Negeri 2 Kelara. The researcher used a pre-experimental approach with a quantitative design in analyzing the data. The instrument used was a speaking test consisting of a pre-test, treatment, and post-test. The population was class VII students and the sample was class VII.1 which was selected using a total sampling technique. The total number of students was 25 students. The results showed that after implementing the collaborative learning method in English learning, it could improve students' Speaking Performance in Fluency and Accuracy in class VII.1 SMP Negeri 2 Kelara. This is evidenced by the average value of students who experienced an increase in pre-test students on fluency got 33.76 and post-test got 40.08. In addition, pre-test students on accuracy got 40.80 and post-test got 54.12. From the results of testing the hypothesis of this research are Pair 1, namely pre-test and post-test fluency is 0.000 (p < 0.05) and vocabulary in Pair 2, the significance value (2-tailed) from pre-test to post-test is 0.000 (p < 0.05). Therefore, the used of the Collaborative Learning Method has a significant effect on improving Speaking Performance in fluency and accuracy in class VII.1 at SMP Negeri 2 Kelara.